Bypass protein-Theory and concept - D.L. Harmon; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1986)
The ruminant animal has the unique advantage of microbial digestion in the rumen. This relationship between host animal and microbial population presents some unique advantages and disadvantages to the animal in terms of using dietary nutrients. The greatest advantage, obviously, is the utilization of dietary fiber. The microbes digest these feedstuffs and derive energy for their growth and maintenance while producing volatile fatty acids for the energy needs of the host animal. Other important products of this microbial digestion are the microbes themselves. They supply the major portion of the animal's protein needs as microbial protein. However, it is inefficient to feed an animal natural protein. The microbes also have the ability to utilize compounds such as urea to provide nitrogen for the synthesis of microbial protein, when dietary protein is less digestible to them. The term "bypass protein" describes dietary protein that, either by some means of alteration or because of type of protein, is resistant to degradation by the rumen microbes. This undigested dietary protein would "bypass" the rumen and would be potentially available to meet the protein needs of the host animal after digestion in the small intestine.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Bypass protein; Animal performance; Rumen microbes